2007
DOI: 10.3184/030823407x266199
|View full text |Cite
|
Sign up to set email alerts
|

New Synthesis of 1,3-diaryl-4-nitro-1-butanones by Microwave-Promoted Michael Addition of Nitromethane to Chalcones without Solvent

Abstract: The Michael addition of nitromethane to chalcones promoted by microwave irradiation without solvent afforded 1,3-diaryl-4-nitro-1-butanones in good yield. The products were characterised by IR, 1 H NMR and elemental analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Because ethanol in this reaction acted as a reactant and solvent, other alcohols, such as MeOH, i-PrOH and n-BuOH, were also attempted for the synthesis of 3a. However, no better yield of 3a was observed compared with ethanol (entries [11][12][13].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Because ethanol in this reaction acted as a reactant and solvent, other alcohols, such as MeOH, i-PrOH and n-BuOH, were also attempted for the synthesis of 3a. However, no better yield of 3a was observed compared with ethanol (entries [11][12][13].…”
Section: Resultsmentioning
confidence: 97%
“…As one of the main classes of ketone compounds, γnitro ketones are widely used as intermediates for the synthesis of various functionalized carbocycles. [3][4][5][6][7][8] The reported typical synthetically viable procedures for the construction of γ -nitro ketones include: i) the conjugate addition of nitromethane to chalcone; [9][10][11][12][13] ii) the detrifluoroacetylative Michael addition of 1-trifluoromethyl-1,3-diketones to conjugated nitroalkenes; 14 iii) the amine-catalyzed Michael addition of ketones to nitrostyrene; [15][16][17][18][19][20][21][22][23][24][25] iv) the nickel-catalyzed decarboxylative Michael addition of β-ketoacids to nitrostyrenes 26,27 (Scheme 1). However, some drawbacks, such as low yield, limited diversity and expensive substrates, still remains in the existing methods.…”
Section: Introductionmentioning
confidence: 99%
“…These potential synthons undergo enantioselective reduction to produce a class of chiral building blocks that are important for the synthesis of heterocyclic compounds. 17 Therefore, the need to develop novel approaches is significant and the Michael addition reaction has been used with enormous success for the synthesis of this kind of compound. As per earlier reports, Nakano et al reported asymmetric Michael addition of -ketoesters with -nitro olefins using amino amide organocatalyst, 18 and Rachwalski et al reported the highly enantioselective synthesis of Michael adducts catalyzed by phosphinoyl-aziridines.…”
Section: Letter Synlettmentioning
confidence: 99%